(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Despite the high incidence of coincident spinal degenerative changes due to the high dynamic interplay between adjacent spinal elements leading to the clinical pain syndromes, yet the diagnostic approach and therapeutic options are still diverse and often inconsistent. Objective: To evaluate the short and long term outcome of two different surgical approaches in the treatment of lateral lumbar disc prolapse associated with spondylosis. Methods: Twenty patients presenting with a comparable complaints of radicular low back pain falling in the age group of 40-50 who attended the outpatient clinic in Science and Technology Hospital in Sanaa from 1st January 2008 to 1st of June 2009 and who were diagnosed to have lumbar lateral disc prolapse with mild spondylotic changes in need for surgery were divided into two groups. Group A offered microdiscectomy while group B offered standard discectomy. They were followed up and evaluated both clinically and radiologically at fixed postoperative intervals (day of discharge, three months, and one year post operatively). Results: It has been revealed that most of cases showed improvement of their presenting complaints due to the acute decompression offered to the neural tissue by either approach though was initially much higher with the minimally invasive microdiscectomy. However, the picture changed at three months interval where (30%) of patients from group A had complaints, two cases (66.6%) of the incompletely responding cases presented with new symptoms mostly due to incompletely treated spondylotic changes and 1 patient (33.3%) of the incompletely responding cases presented with persistence of symptoms due to incomplete disc removal. In contrast, only one case from group B had the persistence of symptoms, which was due to the effect of spondylosis. With further follow up at 1 year interval 40% of cases from group A had complaints mostly in form of bilateral radiating pain due to incompletely treated spondylotic changes, while only (20%) from group B had complaints either as ipsilaterally radiating pain due to incomplete disc resection or as bilaterally radiating pain due to postoperative adhesions. Conclusion: Treatment with the first modality though has the advantages of a shorter duration of surgery, less invasion, less postoperative stay at hospital and comparable clinical response on short term follow up to that of second group, yet data at long term follow up showed that it is associated with a higher incidence of recurrence or incomplete resolve of the presenting complaint as well as evident evolving radiological complications in contrast to treatment by the second modality. Keywords: Lateral disc prolapse, spondylosis, micro discectomy, standard discectomy. DOI: 10.22578/IJMS.14.4.10